Logistic infrastructure and its role in economic security of regions - Kuhan, Sviatlana (Współczesne Problemy Zarządzania, 2018)
The logistics infrastructure actively influences the growth of economic and social indicators of the regions of the republic. The effectiveness of efforts to ensure economic security and competitiveness of the regions depends critically on the rationality and coherence of the organizational and economic regulators used by the direct subjects of transport and forwarding services, as well as by the bodies of the republican and regional government.